Secure encryption algorithms for wireless sensor networks based on node trust value. Issue 3 (4th April 2020) - Li, Li
The data transmission in the wireless sensor network is affected by the forwarding randomness of the relay node, resulting in poor security encryption performance. In order to improve the security encryption capability of wireless sensor network, a wireless sensor network security encryption algorithm based on node trust value is proposed. The linear coding design of sensor network transmission data is carried out according to the trust degree and the composite chaotic model is used for recursive analysis of vector quantisation in wireless sensor network encryption process and then the linear block code design of encryption key and decryption key is realised. The regression analysis results of node trust value are used to realise wireless sensor network security encryption. Simulation results show that the security of wireless sensor network encryption used proposed method is better, the distortion of encrypted transmission is lower and the performance is better.